Exploring the New Moon during the Time of Prophet Muhammad Using Digistar 6 Planetarium - Nurkhanif, Muhammad; Djamaluddin, Thomas; Izzuddin, Ahmad; Ahmad, Mohd Razlan (International Journal Ihya' 'Ulum al-Din, 2024)
This article aims to present a digital visualization of the new moon (hilal) as a determinant of the beginning and end of Ramadan fasting, exploring the astronomical phenomenon of hilal visibility during the Prophet Muhammad's era using the Digistar 6 system in a planetarium. Several Islamic jurisprudence (fiqh) literatures discuss comparisons of fasting durations during the Prophet's time, ranging between 29 and 30 days. This study employs a qualitative research method based on library research, utilizing an astronomical approach and simulation observations in a planetarium. The data used include historical and astronomical data from the Prophet Muhammad's era, as well as related classical literature. The findings of the study include the integration of Digistar 6 technology with computational data to reconstruct the hilal phenomena of the Prophet’s time. For instance, the elevation of the hilal marking the beginning of Syawal in 8 AH was observed at a minimum Moon Altitude of 02°06’22” above the horizon, with an elongation of 04°55’56” and an atmospheric clarity of 9.52%. The Prophet Muhammad observed Ramadan fasting nine times, with six instances involving 29 days of fasting and the remaining three involving 30 days, as determined through simulated physical imagery of the hilal.